The Comparison of Statement Analysis on Disney Case Using Naive Bayes, SNM, and Logistic Algorithm Methods - Rizkiyanti Choirunnisa; Budi Prasetiyo (Journal of Student Research Exploration, 2026)
The Walt Disney Company or also known as Disney, is one of the most famous companies in the world that focuses on the production of animation and film. Disney has been serve in this entertainment industry for over 90 years. Since Disney’s first film was released, Disney was become very famous until this day, especially when Disney has collaborates with many companies, it’s not only focusing on animation production but also making films and many live-action versions of the animations. Recently, Disney has been a hot topic among Disney’s movie fans due to the selection of actors for live action movie characters. Therefore, on this time, the author will conduct a sentiment analysis of Disney using analysis methods called Naïve Bayes, Support Vector Machine, and Logistic Algorithm. After passing through all the testing stages, the highest accuracy result is analysis using the Support Vector Machine (SVM) method. The test results show a high accuracy of 0.60 or 60% with the highest F1-Score in the Positive sentiment class by 67%.